Estado, democracia e controle externo das contratações públicas - Silva Filho, João Antonio da (2023)
This thesis examines the consequences of the performance of the Courts of Auditors in business activity, focusing, in particular, on preventive control as a mechanism for strengthening the performance of the Courts of Auditors in the context of the Democratic Rule of Law. The types of control exercised by the Audit Courts and the legal nature of their judgments are analyzed, also addressing the interference of the Audit Courts' actions in the legal sphere of companies that contract with the Public Power. The impact of large public contracts is examined, evaluating the economic and social impacts of large State contracts, as well as their repercussions on business activity. It focuses on the role of control in building consensus, through the mediation of conflicts between the Administration and contracted companies, as well as conceptual aspects of preventive control as a genre and which, from a temporal perspective, is divided into two types: prior control and concomitant control. This thesis concludes that control is an essential activity in the Rule of Law, with emphasis on the performance of the Courts of Accounts, which has a positive influence on the relationships established between companies and the State, within the field of multidimensional legal interference in the economic phenomenon of entrepreneurship. , above all, in the protection of society and its constitutionalized fundamental rights, especially through preventive control of public contracts, which seeks to prevent the capture of public agents by economic power, and, at the same time, the training of the state as guardian of interests of the community, in order to ensure everyone a dignified existence in accordance with the dictates of social justice.